Marketing violence: the affective economy of violent imageries in the Dutch Republic - Korsten, Frans-Willem (Cambridge elements Elements in histories of emotions and the senses, 2023)
"This Element describes the development of an affective economy of violence in the early modern Dutch Republic through the circulation of images. This title is also available as Open Access on Cambridge Core"--